Atypical Recurrence Presentation of Pre-Transplant Period Multiple Myeloma: Multiple Intracranial Plasmacytomas With Intratumoral Hemorrhage - Yildiz, Abdulkerim; ?nci, Fatih; Köro?lu, Mustafa (Archives of Clinical and Biomedical Research, 2018)
Multiple Myeloma may have extraosseous manifestations in the cranial region. It may be a solitary intracranial tumor (extramedullary plasmacytomas without any other signs of multiple myeloma) or intracranial disease may be a part of generalized disease. We report herein a 65-year-old multiple myeloma patient with the involvement of different regions of brain parancyhma with spontaneous intratumoral hemorrhages. It is an unusual recurrence presentation and unusual situation that intracranial involvements are both with and without dural attachment and all of them have intratumoral hemorrhages.